2009
DOI: 10.1116/1.3122019
|View full text |Cite
|
Sign up to set email alerts
|

Formation of tethered bilayer lipid membranes probed by various surface sensitive techniques

Abstract: Tethered bilayer lipid membranes are promising biomimetic architectures. Their formation has been investigated using four different surface sensitive techniques, including optical, acoustic, and electrical methods. The lipid bilayers are built in a two-step procedure; the proximal layer is formed by self-assembly and is then completed to a bilayer by fusion with small vesicles. The different technical approaches revealed specific aspects of the layer formation processes, namely, first a fast adsorption process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 41 publications
6
72
0
Order By: Relevance
“…Measurements were performed with the Q-Sense E1 instrument (Q-Sense, Gothenburg, Sweden) as described in [21] . Protein solutions (2 mL, 100μg/mL) were pumped through the sensor chamber by a peristaltic pump at a flow rate of 500μL/min.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements were performed with the Q-Sense E1 instrument (Q-Sense, Gothenburg, Sweden) as described in [21] . Protein solutions (2 mL, 100μg/mL) were pumped through the sensor chamber by a peristaltic pump at a flow rate of 500μL/min.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesized anchor lipids were composed of three parts, i.e., a hydrophobic moiety that inserted into the bilayer, a short spacer decoupling the membrane from the substrate, and a surface-specific anchor group ( Figure 3). 9,43 The alkyl chains of the hydrophobic part were modified with diacetylene groups, which enables the cross-linking of the proximal leaflet of the membrane to form diffusion barriers upon polymerization. 26 Long fatty acid chains with diacetylene groups were chosen in order to allow for the formation of a light-sensitive crystal with the ability to polymerize at room temperature.…”
Section: ' Introductionmentioning
confidence: 99%
“…The DE content was varied up to a 0.88 molar fraction; more than this limit, the amine induced disorder of the acyl chains of PC, and we were not able to form a bilayer stable enough to carry out measurements on it. The impedance technique was used in our study to characterize the membrane features as this method has been shown to measure the capacitance and resistance of bilayer lipid membranes accurately [26, 27]. The mean values of the determined parameters were obtained based on six independent measurements of the lipid bilayer.…”
Section: Resultsmentioning
confidence: 99%